Diversity of Fungi in Soils with Different Degrees of Degradation in Germany and Panama. Issue 1 (2nd January 2020) - Rosas-Medina, Miguel; Maciá-Vicente, Jose G.; Piepenbring, Meike
Abstract: Soil degradation can have an impact on the soil microbiota, but its specific effects on soil fungal communities are poorly understood. In this work, we studied the impact of soil degradation on the richness and diversity of communities of soil fungi, including three different degrees of degradation in Germany and Panama. Soil fungi were isolated monthly using the soil-sprinkling method for 8 months in Germany and 3 months in Panama, and characterized by morphological and molecular data. Soil physico-chemical properties were measured and correlated with the observed values of fungal diversity. We isolated a total of 71 fungal species, 47 from Germany, and 32 from Panama. Soil properties were not associated with fungal richness, diversity, or composition in soils, with the exception of soil compaction in Germany. The geographic location was a strong determinant of the soil fungal species composition although in both countries there was dominance by members of the orders Eurotiales and Hypocreales. In conclusion, the results of this work do not show any evident influence of soil degradation on communities of soil fungi in Germany or Panama.